Ameloblastoma of the Sinonasal Tract: Report of a Case with Clinicopathologic Considerations. (28th November 2012) - Tranchina, Maria Grazia; Amico, Paolo; Galia, Antonio; Emmanuele, Carmela; Saita, Vincenzo; Fraggetta, Filippo
Abstract : Ameloblastomas are locally aggressive jaw tumours with a high propensity for recurrence and are believed to arise from remnants of dental lamina or odontogenic epithelium. Extragnathic ameloblastomas are unusual, and primary sinonasal tract origin is very uncommon with few cases reported in the literature. We herein report a case of primary sinonasal ameloblastoma presented in a 74-year-old male with nasal obstruction, rhinorrhoea, and sinusitis. Nasal endoscopy showed the right nasal cavity completely obstructed by a polypoid lesion attached to the lateral nasal wall. A preoperative CT scan was performed showing a solid lesion, measuring 2 cm in the maximum diameter, extending from the nasopharynx area with obstruction of the ostiomeatal unit and sphenoethmoidal recess into the lateral pharyngeal space, laterally to the parotid, without continuity with maxillary alveola and antrum. The tumour was completely excised endoscopically, and a final diagnosis of ameloblastoma was rendered. At the 12-month followup, there was no evidence of recurrence.